Syngas obtained by microwave pyrolysis of household wastes as feedstock for polyhydroxyalkanoate production in Rhodospirillum rubrum - Revelles, Olga (John Wiley and Sons Inc., 2016)

(untitled) (Microb Biotechnol)
The massive production of urban and agricultural wastes has promoted a clear need for alternative processes of disposal and waste management. The potential use of municipal solid wastes (MSW) as feedstock for the production of polyhydroxyalkanoates (PHA) by a process known as syngas fermentation is considered herein as an attractive bio‐economic strategy to reduce these wastes. In this work, we have evaluated the potential of Rhodospirillum rubrum as microbial cell factory for the synthesis of PHA from syngas produced by microwave pyrolysis of the MSW organic fraction from a European city (Seville). Growth rate, uptake rate, biomass yield and PHA production from syngas in R. rubrum have been analysed. The results revealed the strong robustness of this syngas fermentation where the purity of the syngas is not a critical constraint for PHA production. Microwave‐induced pyrolysis is a tangible alternative to standard pyrolysis, because it can reduce cost in terms of energy and time as well as increase syngas production, providing a satisfactory PHA yield.